Efficient Water Spraying Mechanic Design for Eliminating Heat Stress on Biogas Energy Based Dairy Cattle - Sugiono sugiono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The purpose of this paper is to produce an economical water spray driven by cow dung biogas. It is able to remove heat stress from a dairy cow. The initial step for equipment installation is a survey and literature study on the most appropriate water spray points on dairy cow and generation of biogas-fueled electric energy. To produce an economical spray, experiments were performed to determine the change in cow body temperature after sprayed with water for 10 seconds. The maximum output was obtained in 10 seconds spray with 6 minutes interval each with total electrical power required is 0.29 kWh or equal to 0.23m3 biogas.